ENTERPRISE ARCHITECTURE PLANNING SEBAGAI BLUE PRINT SETRATEGI PROMOSI KELOMPOK PENGELOLA USAHA MAHAN TAPIS - Agus Salim; Muhamad Muslihudin; Fauzi Fauzi (Jurnal TAM (Technology Acceptance Model), 2023)
The advancement and development of technology that we enjoy today is the impact of the era of globalization. The existence of technological advances in the business world is marked by the emergence and increase of business actors (MSMEs). The problems that occur in the scope of business actors show that business actors (KPU) in Pringsewu Regency still depend on simple Customer to Customer (C2C) business management. Research conducted by designing Enterprise Architecture Planning for groups of business actors is expected to be able to encourage business progress and business quality such as changes in promotion strategies and sales transactions. Enterprise Architecture Planning (EAP) is a modern approach to planning data quality and achieving information system missions and the steps taken to define the architecture for using information to support business and planning the implementation of that architecture. The results of the research are in the form of system architecture design, interface architecture design, and technology architecture design. The resulting architectural design allows for more open coordination between IT and business units, providing businesses with opportunities to prioritize investments, making it easy to test the current architecture against long-term goals.